Dialogue between the Philosophy of Religion and Science: Dialectics Between Faith and Reason - Malaka, Andi; Albustomi, Ahmad Gibson; Waehama, Muhammad Roflee (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This article explores the dialogue between the philosophy of religion and science, focusing on the dialectics of faith and reason while questioning whether the two are inherently opposed or can be harmonized within a broader framework. Through a qualitative approach grounded in literature review, the study identifies historical harmony and contemporary challenges in integrating faith and reason, highlighting how religious philosophy—from Ancient Greece to Islamic thought—demonstrates their potential complementarity in understanding broader truths. In the modern era, this relationship gains heightened relevance in addressing ethical dilemmas posed by technological and scientific advancements, where religion serves as a moral compass to maintain balance. By incorporating the sociological perspective of religion, the article also examines how religion shapes social structures, norms, and policies, ultimately offering strategic insights into fostering interdisciplinary dialogue that unites intellectual, spiritual, and social traditions in contemporary society. Contribution: This article contributes to the philosophy of religion-science discourse by reframing faith and reason as complementary forces rather than antagonistic opposites. It synthesizes historical, ethical, and sociological perspectives to propose interdisciplinary dialogue as a pathway to addressing modern challenges.